Modern methods of project management for inclusive rural development - Khomiuk, Nataliia (Вежа-Друк, 2023)
Inclusive rural development is important for creating an equal society, as it provides equal access to resources for all residents, promotes social interaction, rural sustainability, and economic development, improves the quality of life of the rural population, and preserves the cultural heritage and traditions of rural communities. The inclusive development of territorial communities in rural areas in the context of decentralization depends on the availability of natural resources, the location of villages, the effective functioning of territorial communities, and the correctness of decisions made by the heads and mayors of these communities. Under current reforms, local governments play a key role in managing the inclusive sphere of territorial communities in rural areas. They coordinate the activities of all economic structures, and participate in the development and implementation of strategies, programs, and projects.
Keywords: inclusive rural development; project management methodologies; Waterfall; Agile approach; 338.43:048.74